Microplastics in Mussels (Mytilus galloprovincialis): Understanding Pollution in Italian Seas - Silva Rubini; Martina Munari; Erika Baldini; Filippo Barsi; Daniela Meloni; Nicola Pussini; Francesca Barchiesi; Gabriella Di Francesco; Carmen Losasso; Cristiano Cocumelli; Salvatore Dara; Sebastiano Virgilio; et al. (Toxics)
Plastic marine litter is a critical issue that threatens marine ecosystems. This study investigated microplastics (MPs) contamination in the Italian seas, involving regions significantly affected by pollution from urban, industrial and agricultural sources. The research, conducted in collaborations between 10 different Experimental Zooprophylactic Institutes throughout Italy, analyzed Mytilus galloprovincialis (common mussels) for its filtration capacity and suitability as a bioindicator. Using data from two projects funded by the Italian Ministry of Health, MPs were detected from 7% to 13% of mussel samples, mainly polypropylene and polystyrene fragments and fibers. These findings align with previous studies highlighting the pervasive presence of MPs and their potential risks as mussels are consumed whole, allowing MPs to be ingested. The study underscores the need for standardized detection methods and coordinated policies to mitigate plastic pollution. Public awareness campaigns and improved waste management practices are key to addressing the environmental and health impacts of MPs. Further research on the long-term effects of MPs on marine ecosystems and human health is essential to developing comprehensive mitigation strategies.